2015
DOI: 10.1111/spsr.12152
|View full text |Cite
|
Sign up to set email alerts
|

“Voluntary PR Voting” in the Election of Swiss Regional Governments

Abstract: This paper analyses citizens' voting behaviour in the April 2011 elections of the regional governments in the cantons of Zurich and Lucerne. These elections were conducted with a majoritarian electoral system in a multi‐member district. In both cantons, the number of candidates in competition is relatively limited due to “voluntary PR”, that is, a coordination effort among parties that aims to achieve a proportional distribution of government seats. If citizens cast all of their votes, they must support candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…More specifically, strategic voting and the coordination by the competitors tend to reduce the number of competitive candidacies to the size of the electoral district (M) plus one (M+1). Empirical studies confirm this hypothesis (Jesse, 1999), and we see it realized in multi-member majoritarian elections in Switzerland (Lutz, 2013; see also Lachat and Kriesi, 2015;Van der Straeten et al, 2018). 8 The crucial difference between majoritarian systems (applied in either single-or multi-member electoral districts) and PR systems is that, in the former, the reduction of the number of competitive candidacies happens at the candidate level, while in the latter, it takes place at the level of party lists.…”
Section: Electoral Incentives For Cross-ethnic Votingsupporting
confidence: 60%
“…More specifically, strategic voting and the coordination by the competitors tend to reduce the number of competitive candidacies to the size of the electoral district (M) plus one (M+1). Empirical studies confirm this hypothesis (Jesse, 1999), and we see it realized in multi-member majoritarian elections in Switzerland (Lutz, 2013; see also Lachat and Kriesi, 2015;Van der Straeten et al, 2018). 8 The crucial difference between majoritarian systems (applied in either single-or multi-member electoral districts) and PR systems is that, in the former, the reduction of the number of competitive candidacies happens at the candidate level, while in the latter, it takes place at the level of party lists.…”
Section: Electoral Incentives For Cross-ethnic Votingsupporting
confidence: 60%
“…The most plausible explanation for this difference is that our study excluded voters who could not evaluate all nine candidates, thus restricting our sample to well-informed voters. Some evidence suggests that lack of information about the candidates is correlated with casting fewer votes (see Lachat and Kriesi 2015). Figure 9.1 provides more information about the number of votes cast by respondents in our sample, showing the distribution of the number of votes for the nine candidates per ballot.…”
Section: Datamentioning
confidence: 86%
“…This, again, strengthens parties' incentives to further reduce the number of candidates. This self-reinforcing process creates an equilibrium in which parties nominate only those candidates with realistic chances of being elected (indirect evidence for such a mechanism is provided by Lutz, 2014;Lachat and Kriesi, 2015). Cox (1990) showed that if partial abstention is the norm, multi-seat majoritarian elections produce convergence of politicians to the center only if the number of candidates is lower or equal to the number of votes plus one.…”
Section: Cantonmentioning
confidence: 99%